2019
DOI: 10.1186/s40360-019-0372-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of apoptosis related genes in nurses exposed to anti-neoplastic drugs

Abstract: BackgroundAnti-neoplastic agents are widely used in the treatment of cancer and some non-neoplastic diseases. These drugs have been proved to be carcinogens, teratogens, and mutagens. Concern exists regarding the possible dangers of the staff handling anti-cancer drugs. The long-term exposure of nurses to anti-neoplastic drugs is still a controversial issue. The purpose of this study was to monitor cellular toxicity parameters and gene expression in nurses who work in chemotherapy wards and compare them to nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…If the inhibition of pyruvate flow is complete, the TCA cycle and OXPHOS would have to stop 108 . It has also been suggested that overexpression of HIF-1α contributes to inhibition of mitochondrial and oxidative damage induced by exposing antitumor drugs 109 . HIF-1α also stimulates catabolism of mitochondrial serine and NADPH production, which regulates mitochondrial redox by transactivation of serine hydroxymethyltransferase 2 and phosphoglycerate dehydrogenase (PHGDH), respectively.…”
Section: Interplay Between Mitochondrial Dysfunctions and Hifsmentioning
confidence: 99%
“…If the inhibition of pyruvate flow is complete, the TCA cycle and OXPHOS would have to stop 108 . It has also been suggested that overexpression of HIF-1α contributes to inhibition of mitochondrial and oxidative damage induced by exposing antitumor drugs 109 . HIF-1α also stimulates catabolism of mitochondrial serine and NADPH production, which regulates mitochondrial redox by transactivation of serine hydroxymethyltransferase 2 and phosphoglycerate dehydrogenase (PHGDH), respectively.…”
Section: Interplay Between Mitochondrial Dysfunctions and Hifsmentioning
confidence: 99%
“…For example, when the nurse came into contact with the patient examined by ECT, the physical examination found different degrees of leukopenia, irregular ecchymosis in the limbs, bleeding gums, and weakness of both lower limbs [24] ; contact patients after 121 I seed implantation will have neurasthenia, blood cell reduction, germ cell apoptosis, and fetal development [25] . In addition to radiation, nurses are also exposed to a large number of anti-tumor drugs, which are clinically used for carcinogenicity, genotoxicity, teratogenicity, reproductive toxicity and organ toxicity [26,27] ,Xiao Hong [28] and Lawson [29] are looked at the same problem and did research and found the exposure of chemotherapy drugs can cause lymphocyte chromosome changes, DNA breakage, increase the risk of cancer in the contact, and may cause primary ovarian dysfunction or failure and amenorrhea. The possibility of abortion after exposure to antineoplastic drugs is twice as high as before.…”
Section: Occupational Exposurementioning
confidence: 99%
“…Regarding the safety of occupational contact with antineoplastic agents, many studies have been conducted (Ramazani et al, 2019; Santos et al, 2020). However, there are a few systematic reviews about the relationship between occupational contact with antineoplastic agents and adverse pregnancy outcomes (Connor et al, 2014; Dranitsaris et al, 2005; Quansah & Jaakkola, 2010).…”
Section: Introductionmentioning
confidence: 99%